Comparison of the Efficacy and Safety of Disease‐Modifying Antirheumatic Drugs Combination Therapies: A Systematic Review and Network Meta‐Analysis - Linfeng Liu; Kaori Ambe; Mayu Onishi; Yuka Yoshii; Toshiaki Makino; Masahiro Tohkin (Clinical and Translational Science)
ABSTRACT There are several disease‐modifying antirheumatic drugs currently available to treat rheumatoid arthritis (RA). However, the optimal combination therapy with methotrexate for treating RA remains unclear. We aimed to identify combination therapies with high‐efficacy and safety by employing the Bayesian method in a network meta‐analysis. We systematically searched PubMed, Embase, CENTRAL, Ichushi web, and PMDA review reports and application materials through October 2020, and found 86 randomized controlled trials. The primary efficacy outcome was the 50% improvement rate according to the American College of Rheumatology criteria (ACR50), and the primary safety outcome was the incidence of serious adverse events. We calculated odds ratios (ORs) and its 95% credible intervals (CrIs) between each treatment, and the surface under the cumulative ranking curve (SUCRA) score for each treatment to rank disease‐modifying antirheumatic drug combinations. Individually, most disease‐modifying antirheumatic drugs combined with methotrexate are more likely to achieve ACR50 than methotrexate monotherapy, with significant differences (p < 0.05), whereas the incidence of serious adverse events was not significantly different compared with methotrexate monotherapy (p > 0.05). Infliximab combined with methotrexate had the highest efficacy ranking (OR = 10.53, 95% CrI: [3.20, 42.87], SUCRA score: 0.884), and etanercept combined with methotrexate had the highest safety ranking (OR = 0.29, 95% CrI: [0.03, 2.04], SUCRA score: 0.893). Comprehensive cluster analysis revealed that the combination of etanercept, an Fc‐fusion protein targeting tumor necrosis factor α, with methotrexate demonstrated higher efficacy and safety. These findings could support the selection of combination therapies for the treatment of RA.